Danby Pickering, ed., The Statutes at Large, from the Fifteenth Year of King Edward III to the Thirteenth Year of King Hen. IV, inclusive, vol. 2 (Cambridge, UK: Joseph Bentham, 1762), 414-15. Cap. XII—Certain Restraints Laid on Wholly Born Welshmen. Passed 1400 (anno secundo Henrici IV) - (:unkn) unknown (General Publisher)
Prohibited Welshmen from bearing any armour with cities, boroughs, or merchant towns. Violators forfeit said armour and imprisoned until a fine is paid on their behalf.
--
Keywords: CARRY